Procedural complications, rehospitalizations, and repeat procedures after catheter ablation for atrial fibrillation - Shah, Rashmee U; Freeman, James V; Shilane, David; Wang, Paul J; Go, Alan S; Hlatky, Mark A (Journal of the American College of Cardiology, 2012)
The purpose of this study was to estimate rates and identify predictors of inpatient complications and 30-day readmissions, as well as repeat hospitalization rates for arrhythmia recurrence following atrial fibrillation (AF) ablation. AF is the most common clinically significant arrhythmia and is associated with increased morbidity and mortality. Radiofrequency or cryotherapy ablation of AF is a relatively new treatment option, and data on post-procedural outcomes in large general populations are limited. Using data from the California State Inpatient Database, we identified all adult patients who underwent their first AF ablation from 2005 to 2008. We used multivariable logistic regression to identify predictors of complications and/or 30-day readmissions and Kaplan-Meier analyses to estimate rates of all-cause and arrhythmia readmissions. Among 4,156 patients who underwent an initial AF ablation, 5% had periprocedural complications, most commonly vascular, and 9% were readmitted within 30 days. Older age, female, prior AF hospitalizations, and less hospital experience with AF ablation were associated with higher adjusted risk of complications and/or 30-day readmissions. The rate of all-cause hospitalization was 38.5% by 1 year. The rate of readmission for recurrent AF, atrial flutter, and/or repeat ablation was 21.7% by 1 year and 29.6% by 2 years. Periprocedural complications occurred in 1 of 20 patients undergoing AF ablation, and all-cause and arrhythmia-related rehospitalizations were common. Older age, female sex, prior AF hospitalizations, and recent hospital procedure experience were associated with a higher risk of complications and/or 30-day readmission after AF ablation.